Oksitocyn Massage and Decreasing Height of Uterin Fundus in Multiparous Women - Elisa Elisa; Iis Sriningsih; Irmawati Irmawati (Jurnal Riset Kesehatan, 2014)
Uncontrolled hemorrhage that contributes for approximately 20 % -25 % of maternal death makes it the most serious risk. The efforts to prevent hemorrhage postpartum can be done since the third and fourth stage of delivery by giving oxytocin through oral, intra - nasal , intra - muscular , or with a massage that stimulates the release of oxytocin hormone, which cause the involution process. This study aims to determine the effect of oxytocin massage on uterine involution to woman with multiparous postpartum. Research design was an experimental Quasy Case control with 36 respondents. The results shows that the treatment mean from the measurement of the reduction of TFU in the 7th (seven) days was 8.56, the mean of group control was 6.33, p value was 0.0001, t value was 4.919. In conclusion, the oxytocin massage significantly decrease of the Height Uterin Fundus in multiparous postpartum women. While on the remeasurement on the 14th day the treatment mean was 10.00, mean value of control was 9.50, p value was 0.038, t value was 2.513 means that oxytocin massage is no longer significantly decrease the Hight Uterin Fundus for women with multiparous postpartum.